2003
DOI: 10.1046/j.1524-4733.2003.65243.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Characteristics and Impact of Laryngopharyngeal Reflux Disease on Health-Related Quality of Life

Abstract: A disease-specific instrument to assess the impact of LPR on HRQL would contribute to clinical care and the evaluation of new therapies. This instrument would ideally be sensitive to the variety of LPR's symptomatic presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 25 publications
3
44
0
1
Order By: Relevance
“…Thus vocal problems can precipitate negative psychological, emotional and social consequences for affected individuals (23). The greatest impact of LPR is likely to be in the area of social functioning, although emotional and psychological well being and role performance might also be significantly affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus vocal problems can precipitate negative psychological, emotional and social consequences for affected individuals (23). The greatest impact of LPR is likely to be in the area of social functioning, although emotional and psychological well being and role performance might also be significantly affected.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest impact of LPR is likely to be in the area of social functioning, although emotional and psychological well being and role performance might also be significantly affected. Four key symptoms were identified that affected LPR patients: voice problem, chronic cough, throat clearing, and swallowing difficulties, primarly in the context of social and occupational environments.LPR symptoms appear to lead to substantial psychological, emotional and social problems (23). Cesari et al led to the hypothesis of a possible correlation between duration of the reflux and dysfunction of the arytenoid muscles, upon which chronic vocal fatigue, with consequent laryngeal compensatory stress, depends (24).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although multiple instruments are available to assess the impact of GERD on adults' quality of life, no specific instruments are available for LPR [56]. The development of such measures will contribute to the appropriate evaluation of new and existing therapies and patient management strategies.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…In addition to suffering from heartburn and abdominal pain, patients may worry that these symptoms represent an early warning sign of cancer (7). Hence, the effect of PPI therapy on HRQOL is an important component of treatment (5).…”
Section: Introductionmentioning
confidence: 99%